Anticancer substances of mushroom origin - Ivanova, T.S.; Krupodorova, T.A.; Barshteyn, V.Y.; Artamonova, A.B.; Shlyakhovenko, V.A. (Experimental Oncology, 2014)
The present status of investigations about the anticancer activity which is inherent to medicinal mushrooms, as well as their biomedical potential and future prospects are discussed. Mushroom products and extracts possess promising immunomodulating and anticancer effects, so the main biologically active substances of mushrooms responsible for immunomodulation and direct cytotoxicity toward cancer cell lines (including rarely mentioned groups of anticancer mushroom proteins), and the mechanisms of their antitumor action were analyzed. The existing to date clinical trials of mushroom substances are mentioned. Mushroom anticancer extracts, obtained by the different solvents, are outlined. Modern approaches of cancer treatment with implication of mushroom products, including DNA vaccinotherapy with mushroom immunomodulatory adjuvants, creation of prodrugs with mushroom lectins that can recognize glycoconjugates on the cancer cell surface, development of nanovectors etc. are discussed. The future prospects of mushroom anticancer substances application, including chemical modification of polysaccharides and terpenoids, gene engineering of proteins, and implementation of vaccines are reviewed. Key Words: mushrooms, anticancer substances, extracts, vaccinotherapy.